Business Process Management Theory and Applications - Glykas, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Business Process Management (BPM) has been in existence for decades. It  uses, complements, integrates and extends theories, methods and tools from  other scientific disciplines like: strategic management, information technology, managerial accounting, operations management etc. During this period the main focus themes of researchers and professionals in BPM  were: business process modeling, business process analysis, activity based costing, business process simulation, performance measurement, workflow management, the link between information technology and BPM for process automation etc. More recently the focus moved to subjects like Knowledge Management, Enterprise Resource Planning (ERP) Systems, Service Oriented Architectures (SOAs), Process Intelligence (PI) and even  Social Networks. In this collection of papers we present a review of the work and the outcomes achieved in the classic BPM fields as well as a deeper insight on recent advances in BPM. We present a review of business process modeling and analysis and we elaborate on issues like business process quality and process  performance measurement as weel as their link to all other organizational aspects like human resources management, strategy,  information technology (being SOA, PI or ERP), other managerial systems, job descriptions etc. We also present  recent advances to BPR tools with special focus on information technology, workflow, business process modeling  and human resources management tools. Other chapters elaborate on the aspect of business process and organizational costing and their relationship to business process analysis, organizational change and reorganization. In the final chapters we present some new approaches that use fuzzy cognitive maps and a recently developed software tool for scenario creation and simulation in strategic management, business process management, performance measurement and social networking. The audience of this book is  quite wide. The first chapters can be read by professionals, academics and students who want to get some basic insight into the BPM field whereas the remaining present more elaborate and state of the art  concepts methodologies and tools for an audience of a  more advanced level.  .
1. John Krogstie. Perspectives to Process Modeling -- Perspectives to Process Modeling -- 2. Matthias Lohrmann and Manfred Reichert. Understanding Business Process Quality -- Understanding Business Process Quality -- 3. E. Sezenias. Alexandros Farmakis and Giorgos Karagiannis, Evi Diagkou, Michael Glykas -- A Hollistic Business Performance Measurement Network -- 4. Ozcelick. Do Business Process Reengineering Projects Payoff? Evidence from the United States -- Do Business Process Reengineering Projects Payoff? Evidence from the United States -- Do Business Process Reengineering Projects Payoff? Evidence from the United States -- 5. Bandar Alhaqbani, Michael Adams, Colin J. Fidge and Arthur H.M. ter Hofstede. Privacy- Aware Workflow Management -- . Privacy- Aware Workflow Management -- . Privacy- Aware Workflow Management -- 6. Apostolia Plakoutsi, Georgia Papadogianni, Michael Glykas. Integrating Human Resource Management, Process Management and Workflow Concepts and Tools for Holistic Planning and Monitoring of Business Performance -- Apostolia Plakoutsi, Georgia Papadogianni, Michael Glykas. Integrating Human Resource Management, Process Management and Workflow Concepts and Tools for Holistic Planning and Monitoring of Business Performance -- Apostolia Plakoutsi, Georgia Papadogianni, Michael Glykas. Integrating Human Resource Management, Process Management and Workflow Concepts and Tools for Holistic Planning and Monitoring of Business Performance -- 7. Bela Mutschler and Manfred Reichert. Understanding the Costs of Business Process Management Technology -- . Understanding the Costs of Business Process Management Technology -- . Understanding the Costs of Business Process Management Technology -- 8. Effimia Pappa, Michail Giakoumis, Viktoria Voxaki, Michael Glykas. Managing Organisational Intellectual Capital -- Effimia Pappa, Michail Giakoumis, Viktoria Voxaki, Michael Glykas. Managing Organisational Intellectual Capital -- Effimia Pappa, Michail Giakoumis, Viktoria Voxaki, Michael Glykas. Managing Organisational Intellectual Capital -- -- 9. Efthymios Constantinides, Carlota Lorenzo-Romero, Maria-del-Carmen Alarcon-del-Amo. Social Networking Sites as business tools: A Study of User Behavior -- 10. G. Stakias. M. Psoras and M. Glykas. Fuzzy Cognitive Maps in Social Networks and Organisational Networking for Business Process Management -- 11. E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- Fuzzy Cognitive Maps in Social Networks and Organisational Networking for Business Process Management -- 11. E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- Fuzzy Cognitive Maps in Social Networks and Organisational Networking for Business Process Management -- 11. E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- E. Papageorgiou. Review study on Fuzzy Cognitive Maps and their applications during the last decade -- 12. Peter P. Groumpos and Ioannis E. Karagiannis. Mathematical Modelling of Decision Making Support Systems Using Fuzzy Cognitive Maps -- . Mathematical Modelling of Decision Making Support Systems Using Fuzzy Cognitive Maps -- . Mathematical Modelling of Decision Making Support Systems Using Fuzzy Cognitive Maps -- 13. Michael Glykas. Fuzzy Cognitive Strategic Maps in Business Process Performance Measurement -- Fuzzy Cognitive Strategic Maps in Business Process Performance Measurement -- Fuzzy Cognitive Strategic Maps in Business Process Performance Measurement -- 14. Siaw Ming Wong, Jean-Yves Lafaye, Patrice Boursier. Capturing domain-imposed requirements based on basic research findings -- , Jean-Yves Lafaye, Patrice Boursier. Capturing domain-imposed requirements based on basic research findings -- , Jean-Yves Lafaye, Patrice Boursier. Capturing domain-imposed requirements based on basic research findings -- -- 15. Μ. Bevilacqua, F.E. Ciarapica, G. Giacchetta.. BPR methods applied to a manufacturer in the domotics sector -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . . . .. .. .. BPR methods applied to a manufacturer in the domotics sector -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . . . .. -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . .<. Managing the SME Clustering Process Life-cycle. . .. BPR methods applied to a manufacturer in the domotics sector -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . . . .. -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . . . Managing the SME Clustering Process Life-cycle. . -- 16. Christina Ampantzi, Marianthi Psyllou, Evi Diagkou, Michael Glykas. Managing the SME Clustering Process Life-cycle. . . . Managing the SME Clustering Process Life-cycle. . Managing the SME Clustering Process Life-cycle. .
Keywords: Computational intelligence; Artificial intelligence; Information technology; Business—Data processing; Computational Intelligence; Artificial Intelligence; IT in Business